Taishō Shōwa nenkan fuken tōkeisho shūsei = Collection of the statistical annuals of the respective prefecture of Japan, 1913-1945 (Yūshōdō Shoten, 1966)
Microfilm reproductions of ca. 4550 vols. of prefectural statistics for Taishō and Shōwa era.